2018
DOI: 10.1177/1742271x18793919
|View full text |Cite
|
Sign up to set email alerts
|

A preclinical ultrasound method for the assessment of vascular disease progression in murine models

Abstract: Introduction: Early detection of vascular alterations associated with disease can play a key role in diagnosis and evaluation of treatment strategies. Ultrasound is commonly used for real-time assessment of human blood vessels but the efficacy of preclinical ultrasound at providing a quantitative assessment of mouse models of vascular disease is relatively unknown. In this study, preclinical ultrasound was used in combination with a semi-automatic image processing method to track arterial distension alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…In the current study, a significant raise in the IJV's pressure in patients with MS compared to healthy individuals was observed. Increasing venous pressure in the superior sagittal sinus in MS A c c e p t e d A r t i c l e patients has been also reported by Bateman et al [24,25]. In this study, the radial strain of the CCA wall in patients with RRMS and PPMS was reduced by 38% and 25%, respectively.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the current study, a significant raise in the IJV's pressure in patients with MS compared to healthy individuals was observed. Increasing venous pressure in the superior sagittal sinus in MS A c c e p t e d A r t i c l e patients has been also reported by Bateman et al [24,25]. In this study, the radial strain of the CCA wall in patients with RRMS and PPMS was reduced by 38% and 25%, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, the compliance and distensibility of the IJV were higher in the healthy group, and significantly higher IJV pressure was observed in patients with MS compared to healthy individuals. Increased venous pressure in the superior sagittal sinus in MS patients has also been reported by Bateman et al [ 24 , 25 ]. In this study, the radial strain of the CCA wall in patients with RRMS and PPMS was 38% and 25% lower, respectively, and the elastic modulus of patients with RRMS and PPMS was 47% and 9% higher, respectively, than in healthy individuals.…”
Section: Discussionsupporting
confidence: 65%
“…Importantly, studies have shown that B-mode images presented a higher reproducibility in the measurements of Valsalva’s sinuses in patients with suspected Marfan syndrome [ 48 ]. B-mode has been applied to the analysis of arterial distension of the carotid arteries and the DAAo in preclinical studies of disease [ 21 ]. Measurements of arterial stiffness at different vascular tree sites do not seem to be interchangeable, but there is a correlation [ 49 ].…”
Section: Integrating Applications Of Ultrasonography In the Assessmentioning
confidence: 99%
“…It has been shown that the reduced circumferential strain is correlated with an increased elastin fragmentation in fibrillin-1 hypomorphic mice [ 44 ]. In addition, a novel semi-automatic method for tracking the changes of vessel lumen diameter with B-mode images was also applicable in mouse models of vascular disease by measuring the arterial diameter over the entire B-mode cine loops [ 21 ].…”
Section: Integrating Applications Of Ultrasonography In the Assessmentioning
confidence: 99%
See 1 more Smart Citation